High-Integrity Software - Sennett T. C (Pitman Publishing, 1989)
The twelve chapters come from both professional and academic authorities and constitute essential reading for professional software engineers and systems designers in civil and military establishments. Introduction, Formal Specification and Implementation, Practical Experience with a Formal Verification System, Reliable Programming in Standard Languages, New Speak: A Reliable Programming Language, Program Analysis and Systematic Testing, Program Analysis and Verification, Assurance in High-Integrity Software, Modelling Real-World Issues for Dependable Software, Contractual specification of Reliable Software, Index.